Development of Linktree-Based Learning Media through the Discovery Learning Approach to Improve the Reading Comprehension Ability of Students in Grade V of SD KKM 1 Makassar City : - - Dila, Dila; Munirah, Munirah; Adam, Andi (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to examine the prototype, validity, practicality, and effectiveness of developing a Linktree-based learning media through a discovery learning approach to enhance reading comprehension skills of fifth-grade elementary school students. The research was conducted in KKM I, Makassar City, with Trial I implemented at MI At Taqwa and Trial II at MI Yaa Bunayya. The method employed was Research and Development (R&D) using the Four-D development model. The results indicate that the Linktree-based media prototype presents content not only in textual form but also through instructional videos and historical videos relevant to the subject matter, supplemented by interactive quizzes to foster engaging and interactive learning. The media and content validation results fall into category D with a reliability value of 1 based on Gregory’s test. Media practicality is demonstrated by observation scores averaging 1.00, teacher response questionnaires averaging 0.93, and student response questionnaires averaging 0.99, with an overall practicality average of 0.97%. The media’s effectiveness is reflected in the improved reading comprehension scores: in Trial I, from 56–65 to 78, and in Trial II, from 69–80 to 80–96. These results confirm that the Linktree-based learning media through a discovery learning approach is more effective than conventional textbook-based learning.